"Alternative solutions for the alternative society": labor and neoliberalism in Nadine Gordimer's The Pickup. Issue 4 (2nd October 2021) - Jewell, Josh
Abstract: In postcolonial criticism of South African fiction there is both a failure to account for the material realities of the present and an overhasty desire to think beyond it to the future. In this article, I look at how Nadine Gordimer's The Pickup (2001) represents the material continuities of apartheid in the form of clientelistic, dependent labor. Whilst the progressive protagonist Julie believes she can live in an "alternative society" with her illegal immigrant partner Ibrahim outside the imperatives of the rapidly corporatizing South Africa, this is revealed to be a fantasy that simply reproduces the indentured conditions of Ibrahim's existence. In both form and content, The Pickup attacks the naïve desire to live outside of the contingencies of contemporary South Africa.